WELFARE, ECONOMIC LITERACY, TEACHER COMMITMENT, AND ECONOMIC RATIONALITY OF ECONOMICS TEACHERS IN EAST JAVA: THE MEDIATING ROLE OF PROFESSIONAL ABILITY - Mazidah, Nur; Wahyono, Hari; Sri Andayani, Endang (Jurnal Pendidikan Ilmu Sosial, 2025)
The creation of effective education can guide students to develop their potential optimally. The focus in developing this potential is to create individuals who are faithful and pious, physically and mentally independent, have noble character, are intelligent and talented, and are holistically healthy. However, there are still problems experienced by teachers related to rational decisions that should be taken. This study focuses on Economic Rationality in high school economics teachers. It is generally known that high school economics teachers should better understand the concept of rationality so that it can be applied in everyday life and used as a model for colleagues and students. This study uses a quantitative approach with an explanatory type that analyzes the influence of Welfare, Economic Literacy, and Teacher Commitment on Economic Rationality with Professional Capability as a mediating variable. The population of this study was economics teachers at Senior High Schools (SMA) and Madrasah Aliyah (MA) in Regencies/Cities throughout East Java in 2024. Sampling using multistage random sampling showed a significant influence between Welfare, Economic Literacy, and Teacher Commitment on the Economic Rationality of Senior High School Teachers in East Java through Professional Ability as a mediating variable.